Chrystologiczna argumentacja w Mowach obronnych przeciw tym, którzy odrzucają święte obrazy Jana Damasceńskiego - Pyc, Marek (Poznańskie Studia Teologiczne, 2011)
In the face of the escalating Iconoclast heresy in the 8th century there appeared the necessity of establishing whether the veneration of icons is justifiable from the Christian viewpoint. The debate primarily concerned the Christological question of venerating Jesus Christ’s icons. St. John of Damascus (675–749) is considered to be one of the most outstanding defenders of sacred icons. We owe to him the first Catholic theology of the icon. His work, „The Defence speeches against those who reject sacred icons” constitutes the answer given to the iconoclasts. The most important argument justifying the veneration of icons is the mystery of the incarnation of the Son of God being the image of the invisible God. The incarnation which liberates one from idolatry lies at the root of a positive vision of matter. John of Damascus refers to the ancient Christian tradition of icon veneration recognizing the word and the image as its essential elements. His teaching would play a key role during the Council of Nicaea in 787.